Generation of high-yield insulin producing cells from human-induced pluripotent stem cells on polyethersulfone nanofibrous scaffold. (31st October 2018) - Mansour, Reyhaneh Nassiri; Barati, Ghasem; Soleimani, Masoud; Ghoraeian, Pegah; Nouri Aleagha, Maryam; Kehtari, Mousa; Mahboudi, Hossein; Hosseini, Fatemeh; Hassannia, Hadi; Abazari, Mohammad Foad; Enderami, Seyed Ehsan
Abstract: Transplantation of islet is a promising method in treatment of patients with type 1 diabetes mellitus (T1DM), however, is limited by islet shortage. The aim of this study was to prepare a polyethersulfone (PES) nanofibrous scaffolds to evaluate the pancreatic differentiation of human induced pluripotent stem cells (hiPSCs). The differentiation process in tissue culture dishes and PES scaffolds was evaluated at mRNA and protein level by RT-qPCR and immunofluorescence assay, respectively. The functionality of differentiated cells was determined by insulin and C-peptide release in response to glucose challenges. The results of this study showed that cells cultured on PES nanofibrous scaffolds exhibit more pancreatic β-cell characteristics as they express more pancreatic tissue-specific genes and proteins. Furthermore, the immunoassay showed that differentiated cells in both culture plates and PES scaffolds groups are functional and secrete C-peptide and insulin in response to glucose challenges. Altogether, the results of this study demonstrated that PES nanofibrous scaffold could provide the microenvironment that promotes the differentiation of induced pluripotent stem cells (iPSCs) into insulin producing cells.